The Cultural Messages of Pyramid House in Palembang - Bungsu, Ario; Triyanto, Triyanto; Rohendi Rohidi, Tjetjep (Catharsis, 2020)
Abstract Pyramid House in Palembang is one of the works of art that is still very interesting to be researched today. The problem raised in this study aims to analyze the cultural message of the Pyramid House in Palembang. The method used is a qualitative method with a case study research design. The data collection techniques include observation, interviews, and document study. The results showed that in the manufacture of the Pyramid house, the main construction of traditional buildings used wood construction and a stilt system. The foundation used the construction of piles, the walls used boards, the roof used a leaf or shingle roof. The core parts consisted of the roof of the house, the door, the window, the stairs, and the floor of the house. In general, the typical architectural form of the Pyramid House, namely, the roof was shaped like a severed pyramid. Besides, the uniqueness of the house located in its multi-storey shape (kijing) and the walls were made of wood shaped like planks. Then related to the house name Pyramid, it contained two special meanings, namely, Five and Gold. The word five means the number five, while gold means the precious metal of great value. This is also a symbol of the function of the Pyramid house.